2012
DOI: 10.1186/1471-2350-13-33
|View full text |Cite
|
Sign up to set email alerts
|

The genetic variants at the HLA-DRB1 gene are associated with primary IgA nephropathy in Han Chinese

Abstract: BackgroundImmunoglobulin A nephropathy (IgAN), an immune-complex-mediated glomerulonephritis defined immunohistologically by the presence of glomerular IgA deposits, is the most common primary glomerular disease worldwide and a significant cause of end-stage renal disease. Familial clustering of patients with IgAN suggests a genetic predisposition.MethodsIn this study, 192 patients with IgAN and 192 normal controls in the Sichuan cohort and 935 patients with IgAN and 2,103 normal controls in the Beijing cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
3
12
0
Order By: Relevance
“…These agree with other reports that identical diseases may be associated with different HLA-II alleles in different populations [15,16]. …”
Section: Introductionsupporting
confidence: 93%
“…These agree with other reports that identical diseases may be associated with different HLA-II alleles in different populations [15,16]. …”
Section: Introductionsupporting
confidence: 93%
“…It is known that IgA antibody‐mediated immune response is T‐cell dependant, and the HLA class‐II products coded by DP, DQ, and DR genes affect antigen presentation to particular T cells . Reports from Hong Kong, Taiwan, Guangdong, and Sichuan have revealed HLA ‐family genetic variants to be associated with the genetic susceptibility of IgAN or a special subgroup of IgAN . It has already been reported that there is an association between HLA‐DRB1 polymorphisms and IgAN in the Han Chinese; HLA‐DRB1 * 140501 confers susceptibility, while HLA‐DRB1 * 070101 confers resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Another rapidly evolving area is the knowledge on the genetic basis of IgAN in large populations. Genome-wide association studies have identified associations of single human leukocyte antigen (HLA) polymorphisms [11] and some proinflammatory genes [12] with the development or course of IgAN. More importantly, using such a genetic approach, we can develop a worldmap of IgAN risk [13] ( Fig.…”
Section: Immunoglobulin a Nephropathymentioning
confidence: 99%